PENEGAKAN HUKUM TINDAK PIDANA PENCURIAN SARANG BURUNG WALET OLEH KEPOLISIAN SEKTOR TELUK MERANTI DI KECAMATAN TELUK MERANTI KABUPATEN PELALAWAN - Tambunan, Novrianto; Effendi, Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Crime is an act of unlawful knowingly has been done by someone who can be held accountable for his actions, which otherwise as may be punished. Crime also certain acts, as misconduct or unlawful. Crime is the result of interaction because of the interrelations between the existing and influence each other. One of the criminal act (offense) to be solved legally is the offense of theft. Crimes against theft, especially theft bird nest in Teluk Meranti Pelalawan is a symptom of a very disturbing tranquility, peace and tranquility of society. In this case the role of law enforcement is essential in providing a sense of justice to the people. The purpose of this thesis is; First, to determine the law enforcement against theft bird nest by police Teluk Meranti Pelalawan. Second, to determine the barriers in knowing the law enforcement against theft bird nest by police Teluk Meranti Pelalawan. Third, to know the efforts made to know the law enforcement against theft bird nest by police Teluk Meranti Pelalawan.This research is the study of law or juridical empirical sociological. The location of research is Teluk Meranti Police Jurisdiction Pelalawan. Source of data, supported by the primary data source, secondary data sources, data source tertiary, while data collection technique is interview / interview and review of the literature. After the data collected was then analyzed qualitatively using the deductive method to analyze the problems of a general nature and is then drawn to a conclusion in particular based on existing theory.From the research, there are three things that matter can be concluded, first, to know the law enforcement against theft bird nest by police Teluk Meranti Pelalawan not run well. Second, the barriers faced by law enforcement in the jurisdiction of Police Teluk Meranti Pelalawan; cultures or customs of the people who have hereditary, infrastructure problems, and lack of law enforcement personnel. And prevention efforts undertaken by law enforcement in the area of police hukm Teluk Meranti Pelalawan is law enforcement professionals and high integrity, to cooperate with the community, holding information on the law, the presence of adequate infrastructure and facilities.